2019
DOI: 10.1037/tra0000408
|View full text |Cite
|
Sign up to set email alerts
|

The complexity of trauma exposure and response: Profiling PTSD and CPTSD among a refugee sample.

Abstract: Objective: This study investigated the latent dimensional and categorical structure of ICD-11 Complex Posttraumatic Stress Disorder (CPTSD) within a refugee sample. Method: A subsample that identified as refugee (n = 308) was selected from the National Epidemiological Survey on Alcohol and Related Conditions (NESARC-II). Factor Mixture Modelling (FMM) was employed to establish the dimensional structure of CPTSD symptomology and the categorical distribution of these dimensions. It was then evaluated whether tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

10
58
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 41 publications
(70 citation statements)
references
References 53 publications
10
58
2
Order By: Relevance
“…Indeed, the results of this study are consistent with most of the investigations on clinical samples, which have identified only 2 or 3 classes (on the contrary, four or more classes have been identified in larger community samples), which typically represented a PTSD profile, a CPTSD profile, and, in some cases, a third profile low on all symptoms, describing what might be viewed as a resilient group (Brewin et al, 2017). Moreover, also the other two studies with refugee samples evidenced two classes characterized by symptom profiles that were consistent with ICD-11 CPTSD and PTSD formulations (Frost et al, 2019;Hyland et al, 2018). Therefore, the findings of the present studythe first on a sample of African refugees living in a western countryadd to a large and growing empirical literature supporting the discriminant validity of PTSD and CPTSD amongst multiple samples taken from culturally and trauma diverse backgrounds (see references in the introduction).…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…Indeed, the results of this study are consistent with most of the investigations on clinical samples, which have identified only 2 or 3 classes (on the contrary, four or more classes have been identified in larger community samples), which typically represented a PTSD profile, a CPTSD profile, and, in some cases, a third profile low on all symptoms, describing what might be viewed as a resilient group (Brewin et al, 2017). Moreover, also the other two studies with refugee samples evidenced two classes characterized by symptom profiles that were consistent with ICD-11 CPTSD and PTSD formulations (Frost et al, 2019;Hyland et al, 2018). Therefore, the findings of the present studythe first on a sample of African refugees living in a western countryadd to a large and growing empirical literature supporting the discriminant validity of PTSD and CPTSD amongst multiple samples taken from culturally and trauma diverse backgrounds (see references in the introduction).…”
Section: Discussionmentioning
confidence: 91%
“…institutional child abuse, sexual assault, bereavement, child soldiering, war prisoners). Of these sixteen studies, thirteen offer support for qualitatively distinct classes where symptom profiles are consistent with the distinction between ICD-11 PTSD and CPTSD (Ben-Ezra et al, 2018;Böttche et al, 2018;Cloitre, Garvert, Brewin, Bryant, & Maercker, 2013;Cloitre, Garvert, Weiss, Carlson, & Bryant, 2014;Elklit, Hyland, & Shevlin, 2014;Frost et al, 2019;Karatzias et al, 2017;Knefel, Garvert, Cloitre, & Lueger-Schuster, 2015;Murphy, Elklit, Dokkedahl, & Shevlin, 2016;Palic et al, 2016;Perkonigg et al, 2016;Sachser, Keller, & Goldbeck, 2017;Zerach, Shevlin, Cloitre, & Solomon, 2019). In contrast, the remaining three studies (Eidhof et al, 2019;Glück, Knefel, Tran, & Lueger-Schuster, 2016;Wolf et al, 2015) observed classes that differed quantitatively rather than qualitatively suggesting that CPTSD is not distinguishable from PTSD and that differences in classes are best explained varying degrees of symptom severity on a single, underlying, condition (i.e.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The likelihood of developing PTSD depends on the interaction between individual risk factors (i.e. genetic or epigenetic risks, psychological resiliency) and traumatic load 21 , whereas cumulative trauma exposures have a clear dose-effect relationship with the symptoms of PTSD in a population with high levels of traumatic events [22][23][24] . However, TEC group showed the stronger thalamo-postcentral negative connectivity than PTSD group even after controlling for traumatic load.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, mounting evidence supports the proposition that CPTSD develops after continuous, severe interpersonal trauma exposure, and, expressly, with trauma occurring during childhood (Ben‐Ezra et al., ; Cloitre et al., ; Frost et al., ; Frost, Hyland, Shevlin, & Murphy, ; Hyland et al., ; Palic et al., ; Shevlin et al., ). Research by Hyland, Murphy, and colleagues () suggests that there might be specificity in the associations among trauma exposure, PTSD, and CPTSD: They found that some trauma types were uniquely associated with PTSD (robbery), some uniquely associated with CPTSD (childhood physical abuse), and some were associated with both disorders (childhood sexual abuse).…”
mentioning
confidence: 93%